Images, imagination and the global environment: towards an interdisciplinary research agenda on global environmental images. Issue 2 (26th July 2016) - Grevsmühl, Sebastian Vincent
Abstract : Global environmental images have become part of our everyday life experience. We encounter them in news reports, scientific articles and artistic interventions. Yet so far, only the most iconic of these images have received close critical attention from scholars coming mostly from two related fields, science studies and cultural geography. Some of those studies, as for instance research carried out on the famous Apollo photographs, have revealed that the icons of our environmental age do not provide simple readings, that they carry multiple, often contradicting messages, and that they can be vectors of highly ambiguous and even conflicting political beliefs. However, historically informed interdisciplinary research on visual cultures from an environmental perspective is still at its beginning. This essay thus calls for a systematic exploration of the crucial role the visual plays in the creation, circulation, interpretation and adaptation of global environmental knowledge. It is argued that this inquiry cannot be left solely to historians or geographers but calls for a truly interdisciplinary engagement. One central claim is that we need to better understand the constitutive role the visual and associated knowledge practices, conventions and infrastructures play in mediating global environmental phenomena. One possibility, it is argued, is to develop a broader historical framework for understanding how the visual actively shaped scientific and environmental discourse, and how it stimulated the rise of holistic and dynamic understandings of the environment from the nineteenth century onwards. A second important research area that is suggested concerns the crucial role global environmental images play at the interface of science discourse and environmental policy and governance. The essay concludes by suggesting three basic theses which seem particularly promising for future interdisciplinary inquiries into global environmental images. Abstract : The paper calls for a historically informed interdisciplinary inquiry into global environmental images. e00020